2009
DOI: 10.1371/journal.pone.0005738
|View full text |Cite
|
Sign up to set email alerts
|

How Many Scientists Fabricate and Falsify Research? A Systematic Review and Meta-Analysis of Survey Data

Abstract: The frequency with which scientists fabricate and falsify data, or commit other forms of scientific misconduct is a matter of controversy. Many surveys have asked scientists directly whether they have committed or know of a colleague who committed research misconduct, but their results appeared difficult to compare and synthesize. This is the first meta-analysis of these surveys.To standardize outcomes, the number of respondents who recalled at least one incident of misconduct was calculated for each question,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
1,143
9
75

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,550 publications
(1,258 citation statements)
references
References 47 publications
(78 reference statements)
31
1,143
9
75
Order By: Relevance
“…For instance, a review 2 of 2,047 life-science papers retracted from 1973 to 2012 found that around 43% were attributed to fraud or suspected fraud. A compilation of anonymous surveys 3 suggests that 2% of scientists and trainees admit that they have fabricated, falsified or modified data. And a 1996 study 4 of more than 1,000 postdocs found that more than one-quarter would select or omit data to improve their chances of receiving grant funding.…”
Section: Scale Of Evidencementioning
confidence: 99%
“…For instance, a review 2 of 2,047 life-science papers retracted from 1973 to 2012 found that around 43% were attributed to fraud or suspected fraud. A compilation of anonymous surveys 3 suggests that 2% of scientists and trainees admit that they have fabricated, falsified or modified data. And a 1996 study 4 of more than 1,000 postdocs found that more than one-quarter would select or omit data to improve their chances of receiving grant funding.…”
Section: Scale Of Evidencementioning
confidence: 99%
“…The epilepsy journals, as with others, are littered with their fair share of reports of the success of surgical and medical treatments that cannot possibly be correct, and for these various reasons, it has been claimed that massive misinformation exists in the domain of scientific research. This has become of increasing public concern 39, 40, 41, 42, 43, 44. Goldacre wrote of a litany of dubious practices in relation to pharmaceutical trials including missing data from negative trials that were suppressed, the lack of transparency of data, the problems with outsourcing volunteer studies, statistical errors in trials, the medicalization of behaviors to create diseases that then can be treated, the sophistication of marketing of drugs, the nature of the connections between the academic medical community and commercial interests 45.…”
Section: Why Do We Get It Sometimes Wrong?mentioning
confidence: 99%
“…To date, we have been lucky at JMT, but letting something get published that does not meet our standard of ethical integrity can certainly happen here as has already occurred in most journals. According to some estimates, anywhere from 0.02 to 0.2% of published papers include some degree of fraudulent work or other misconduct [3]-that is, a staggering number when considering that over 28,000 journals publish over 2,000,000 new articles each year.…”
mentioning
confidence: 99%
“…According to a sobering meta-analysis published almost 10 years ago, almost 2% of published scientists "admitted to have fabricated, falsified or modified data or results at least once -a serious form of misconduct by any standard -and up to 33.7% admitted other questionable research practices." [3]. This is why all submissions to JMT are subjected to careful review by experienced editors and content experts, and when numbers are used in a manuscript, we also rely on the talented eye of a statistical editor.…”
mentioning
confidence: 99%
See 1 more Smart Citation